Serpin neuropathology in the P497S UBQLN2 mouse model of ALS/FTD. (29th March 2021) - Higgins, Nicole R.; Greenslade, Jessie E.; Wu, Josephine J.; Miranda, Elena; Galliciotti, Giovanna; Monteiro, Mervyn J.
Abstract: Accumulating evidence suggests X‐linked dominant mutations in UBQLN2 cause amyotrophic lateral sclerosis (ALS) with frontotemporal dementia (FTD) through both loss‐ and gain‐of‐function mechanisms. However, the mechanisms by which the mutations cause disease are still unclear. The goal of the study was to uncover the possible pathomechanism(s) by which UBQLN2 mutations cause ALS/FTD. An analysis of proteomic changes in neuronal tissue was used to identify proteins with altered accumulation in the P497S UBQLN2 transgenic mouse model of ALS/FTD. We then used immunocytochemistry and biochemical techniques to confirm protein changes in the mutant P497S mice. Additionally, we used cell lines inactivated of UBQLN2 expression to determine whether its loss underlies the alteration in the proteins seen in P497S mice. The proteome screen identified a dramatic alteration of serine protease inhibitor (serpin) proteins in the mutant P497S animals. Double immunofluorescent staining of brain and spinal cord tissues of the mutant and control mice revealed an age‐dependent change in accumulation of Serpin A1, C1, and I1 in puncta whose staining colocalized with UBQLN2 puncta in the mutant P497S mice. Serpin A1 aggregation in P497S animals was confirmed by biochemical extraction and filter retardation assays. A similar phenomenon of serpin protein aggregation was found in HeLa and NSC34 motor neuron cells with inactivated UBQLN2 expression. We found aberrant aggregation of serpin proteins, particularly Serpin A1, in the brain and spinal cord of the P497S UBQLN2 mouse model of ALS/FTD. Similar aggregation of serpin proteins was found in UBQLN2 knockout cells suggesting that serpin aggregation in the mutant P497S animals may stem from loss of UBQLN2 function. Because serpin aggregation is known to cause disease through both loss‐ and gain‐of‐function mechanisms, we speculate that their accumulation in the P497S mouse model of ALS/FTD may contribute to disease pathogenesis through similar mechanism(s). Abstract : We found aberrant accumulation and co‐aggregation of serpin proteins, particularly Serpin A1, with UBQLN2 inclusions in the brain and spinal cord of the P497S UBQLN2 mouse model of ALS/FTD. Similar aggregation of serpin proteins was found in UBQLN2 knockout cells suggesting serpin aggregation may stem from a loss of UBQLN2 function. Serpin aggregation is known to cause disease through both gain‐ and loss‐of‐function mechanisms, and we speculate that their accumulation in P497S mice may contribute to disease pathogenesis through similar mechanisms.